The Effect of Work Discipline and Work Ethics on Employee Performance at the Cibeunying Kidul District Office - Junita Pajriani Sinaga; Bulgi Fadla; Shinta Oktafien (Jurnal Ad'ministrare, 2022)
Human resources influence the progress of an agency in carrying out its activities to achieve its goals. Employees are human resources who are in an agency. To provide an increase in the quality of work of employees in an agency by paying attention to work discipline and work ethic of employees. In this paper, research was carried out in the Cibeunying Kidul District Office, Bandung City, where the performance of employees in that office was still relatively low because there were still several employees whose performance targets were not achieved. The purpose of this study is to obtain results from an analysis of the influence of work discipline and work ethic on the work quality of the Cibeunying Kidul District Office, Bandung City. This research uses quantitative techniques through a descriptive approach. The method of taking samples uses saturated sampling and collecting data is done through observation, interviews, and questionnaires. The population and sample in this study are the entire workforces of the Cibeunying Kidul District Office, Bandung City, totaling 57 employees. The data analysis technique used is validity testing, reliability testing, classical assumption testing, and multiple linear regression analysis. The results of this study found that work discipline has a partial effect on employee performance, while work ethic does not affect the work quality of the Cibeunying Kidul District Office, Bandung City. As well as discipline and work ethic simultaneously influence the quality of work of the Cibeunying Kidul District Office, Bandung City